The involvement of extracellular vesicles in the transcytosis of nanoliposomes through brain endothelial cells, and the impact of liposomal pH-sensitivity. (January 2022) - Reginald-Opara, Joy N.; Svirskis, Darren; Paek, Song Yee; Tang, Mingtan; O'Carroll, Simon J.; Dean, Justin M.; Chamley, Lawrence W.; Wu, Zimei
Abstract: Despite the demonstrated effectiveness of nano-materials for drug delivery to the brain, a comprehensive understanding of their transport processes across the blood brain barrier (BBB) remains undefined. This multidisciplinary study aimed to gain an insight into the transport processes across BBB, focusing on the transcytosis of liposomes and the impact of liposomal pH-sensitivity. Glutathione-PEGylated pH-sensitive (GSH-PEG-pSL) and non pH-sensitive liposomes (GSH-PEG-L) were fluorescently labelled with rhodamine-DOPE and calcein, both impermeable to biomembranes. Following exposure to brain microvascular endothelial cells (hBMECs), the key functional component of the BBB, intracellular trafficking were evaluated by confocal live-cell imaging. The exocytosed liposomes, including naturally-occurring extracellular vesicles (EVs), were collected using differential centrifugation and and characterised regarding the EV yield, morphology and EVs origin using nanoparticle tracking analysis, transmission electron microscopy and flow cytometry. The transcytosis of liposomes through a verified BBB model comprising of hBMECs monolayer was also quantified. GSH-PEG-L was initially retained in the endo-lysosomes before exocytosed while packed in EVs of different sizes (<100 ​nm to >1 ​μm) while GSH-PEG-pSL underwent endosome escape with less degree of exocytosis with more fluorescence remaining in the cytoplasm. Compared with the untreated, hBMECs treated with GSH-PEG-L increased the yield of nano-EV and medium-EV by 7.9-fold and 4.6-fold, respectively. Conversely, GSH-pSL-treated cells produced 2.9-fold more nano-EVs but 2-fold less medium-EVs than the control cells. These vesicles were CD144-positive confirming their endothelial cell-origin. GSH-PEG-L demonstrated 2-fold higher efficiencies than GSH-PEG-pSL to cross the in vitro BBB model via exocytosis. Taken together, GSH-PEG-L might utilize EV secretion pathway to achieve transcytosis across brain endothelial cells of the BBB while liposomal pH-sensitivity favors cytoplasmic delivery. Graphical abstract: Image 1